REPRESENTATIONS OF CLIMATE ANXIETY IN RICHARD POWERS' THE OVERSTORY - Fahrezi, Adam Ardian; Agus, Sitti Hasmah; Yudith, Madeline; Harun, Muhammad; Musfirahwaty, Auriza (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
The research analyzes how Richard Powers portrays climate anxiety in The Overstory through an ecocritical framework. The research investigates the emotional and psychological challenges which eight main characters Patricia Westerford, Nick Hoel, Olivia Vandergriff, Douglas Pavlicek, Adam Appich, Neelay Mehta, Ray Brinkman and Dorothy Cazaly experience because of ecological destruction. The characters in the story display different emotional reactions which reflect the ecological crisis through their feelings of fear and guilt and despair and deep anxiety. The research bases its analysis on the rising literary interest in psychological effects of climate change. The research aims to study climate anxiety representation in the novel while demonstrating how ecocriticism helps reveal its complex ethical and emotional aspects. The research employs qualitative methods and thorough textual analysis to demonstrate how multiple narrative perspectives in the novel allow readers to experience environmental crisis through different personal and ethical perspectives. Through its narrative The Overstory prompts readers to reevaluate their natural relationships while showing how literary works can both convey and strengthen shared emotional responses to climate anxiety